The Jolly Christmas Postman - Ahlberg, Janet and Ahlberg, Allan (Penguin Group, 2011)
It's Christmas Eve and the JOLLY POSTMAN is delivering greetings to various fairy-tale characters - there's a card for Baby Bear, a game appropriately called 'Beware' for Red Riding Hood from Mr Wolf, a get-well jigsaw for hospitalised Humpty Dumpty and three more surprise envelopes containing letters, cards, etc. Everyone's favourite postman keeps on peddling his bicycle up hill and down dale . . . and into everybody's hearts.
Keywords: Christmas & Advent; Holidays & Celebrations; Juvenile Fiction